EXPLORATION OF DISTRICT-LEVEL INNOVATIONS TO ADDRESS MATERNAL AND NEONATAL MORTALITY IN INDONESIA - Halimah Halimah; Edward Sutanto; Suparmi Suparmi; Ario Baskoro; Nirwan Maulana; Nadhila Adani; Wahyu Puji Nugraheni; Djunaedi Djunaedi; Farida Aryani; Melyana Lumbantoruan; Trihono Trihono (Indonesian Journal of Health Administration, 2022)
Background: The Indonesian maternal and neonatal mortality rates remain some of the highest in Southeast Asia. Aims: This study aims to assess and compare district-level innovations that address maternal and neonatal mortality. Methods: This was a qualitative study conducted via four focus group discussions in eight selected districts in November 2021. Data obtained were analyzed using the WHO health system building blocks framework. Results: The study found high variation in districts’ innovations ranging from expansion of service for maternity waiting homes to periodical obstetrician visits at Puskesmas. A majority of districts use a local approach as the basis for innovation. Some innovations are modifications of the national program or initiated purely by District Health Offices, Puskesmas, and the community. Many interventions are based on multisectoral commitment, community participation, and targeting to strengthen health service delivery. Leadership and health financing also have an influence on the implementation of these innovations. Conclusion: The multitude of innovations reflects a high variation in barriers to reducing maternal and neonatal mortality that need to be addressed at the district level. A routine forum to share districts’ best practices is warranted. Additionally, family-based surveillance for neonatal danger signs, monitoring for pregnant women and neonates via WhatsApp, and zoning systems for referrals to healthcare facilities in larger districts are innovations identified in this study that have potential to be replicated in other districts or expanded nationally.